Exploiting Post-mitotic Yeast Cultures to Model Neurodegeneration - Ruetenik, Andrea; Barrientos, Antonio (Frontiers in Molecular Neuroscience, 2018)
Over the last few decades, the budding yeast Saccharomyces cerevisiae has been extensively used as a valuable organism to explore mechanisms of aging and human age-associated neurodegenerative disorders. Yeast models can be used to study loss of function of disease-related conserved genes and to investigate gain of function activities, frequently proteotoxicity, exerted by non-conserved human mutant proteins responsible for neurodegeneration. Most published models of proteotoxicity have used rapidly dividing cells and suffer from a high level of protein expression resulting in acute growth arrest or cell death. This contrasts with the slow development of neurodegenerative proteotoxicity during aging and the characteristic postmitotic state of the affected cell type, the neuron. Here, we will review the efforts to create and characterize yeast models of neurodegeneration using the chronological lifespan model of aging, and the specific information they can provide regarding the chronology of physiological events leading to neurotoxic proteotoxicity-induced cell death and the identification of new pathways involved.